2021
DOI: 10.1007/s12282-021-01227-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating B lymphocytes and plasma cells in triple-negative breast cancer

Abstract: Background Recent investigations have demonstrated that the tumor microenvironment, including tumor-infiltrating lymphocytes (TILs), is an important factor in tumor growth and development. While the prognostic correlation of tumor-infiltrating T cells has been widely studied in breast cancer, that of tumor-infiltrating B cells and plasma cells has not received so much attention, especially in triple-negative breast cancer (TNBC). Methods We investigated 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…4 A), while the B regs marker CD1d1 was generally reduced ( Fig. 4 A) [ 22 , 23 ]. Nos2/Cox2 blockade also promoted increased proinflammatory N1 neutrophil biomarkers including myeloperoxidase ( Mpo ), neutrophil elastase ( Elane ) and lactoferrin ( Ltf ) expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 A), while the B regs marker CD1d1 was generally reduced ( Fig. 4 A) [ 22 , 23 ]. Nos2/Cox2 blockade also promoted increased proinflammatory N1 neutrophil biomarkers including myeloperoxidase ( Mpo ), neutrophil elastase ( Elane ) and lactoferrin ( Ltf ) expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to these series of theories, we previously reported that CD20+ TILs may support an increase in CD4+ and CD8+ TILs, altering the anti-tumor response and resulting in a positive prognosis in TNBC [ 5 7 ]. Further, although the prognostic correlation with macrophages has been widely reported in breast cancer, there is no consensus on the prognostic impact [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high abundance of regulatory T cells is significantly associated with high tumor expression levels of immune checkpoint inhibitor genes ( 44 , 45 ), which may explain the effective response of the low CRG_score group to immunotherapy. Although the presence of B cells and plasma cells is a good predictor of patient prognosis ( 46 , 47 ), B cells also have immunosuppressive roles in TNBC by enhancing the levels of myeloid-derived suppressor cells (MDSCs) or promoting IL-10 levels to facilitate isotype conversion to immunosuppressive IgG4 antibodies ( 48 , 49 ). In fact, the effects of the humoral immune response on tumors may not be related to the presence of B cells ( 50 ), but rather depend on the tumor antigen recognition ability and activation of the complement signaling pathway, which ultimately determines the immune phenotype of B cells.…”
Section: Discussionmentioning
confidence: 99%